RISK-BASED APPROACH IN THE EUROPEAN UNION LEGISLATION TO PREVENT MONEY LAUNDERING AND FINANCING OF TERRORISM - CОCIUG, Victoria; ANDRUSCЕAC, Tеоdоr (Economy and Sociology, 2021)
Money laundering and terrorism financing are serious and internationally emerging issues that must be approached and confronted at European Union level. The latest terrorist attacks and periodic banking scandals highlight the necessity for additional attention in this particular direction. In regard to the internal EU market, financial flows are integrated and trans-border by nature, thus funds can circulate rapidly, from one country to another, offering the possibility to perpetrators and terrorists to transfer money across Member State avoiding detection by authorities. This specific situation generates the necessity to identify and understand the particular ML/TF risks generated by services and products offered within the EU economic and financial ecosystem. In order to ensure an efficient mechanism for identifying the ML/TF risks associated with the products and services provided on the territory of European Union, the 4AMLD provides the obligation of the EU Commission to perform once in two years the so-called European Union Money Laundering and Terrorist Financing Supranational Risk Assessment. Since 2017 two supra-national risk assessments were carried out and the final results are used by Member States to monitor the evolution of risks at Union level and to implement the necessary recommendation for ensuring a proper minimization of threats and vulnerabilities at the national level. This paper aims to analyze, understand and compare the main outcomes of the two assessments, namely the identified risks and their links with vulnerable sectors, as well as the evolution or devolution of certain risks as a result of mitigation measures applied by EU Member States. Another task of this article is to provide additional recommendations in terms of mitigating measures and efforts, which must be taken into account by Member States.